Molecular genetic markers of breast cancer - K. A. Grishina; T. A. Muzaffarova; V. A. Khaylenko; A. V. Karpukhin (Опухоли женской репродуктивной системы, 2016)
Breast cancer (BC) is the second most common type of cancer worldwide and affects 1 in 8 women over the course of their lifetime. A personalized approach to treating BC can substantially increase efficiency and consequently maintain the active life of many people. This encourages investigators and physicians to better understand tumor biology in order to make a correct diagnosis, to determine recurrence risk, and to choose adequate therapy. This paper discusses the bases for the molecular classification of BC into its expression subtypes, as well as current prognostic kits that assist oncologists in classifying the subtypes of cancer and in predicting the development of the disease. The existing test systems are not universal, each of them is applicable only to a limited group of patients, but they totally cover a considerable number of cases. The tumor gene mutations in BC, which have been characterized by up-to-date methods, can serve as predictive markers for the efficiency of targeted therapy.